2021
DOI: 10.1177/0969733020983392
|View full text |Cite
|
Sign up to set email alerts
|

The Surprise Question and Serious Illness Conversations: A pilot study

Abstract: Background: Serious Illness Conversations aim to discuss patient goals. However, on acute medicine units, seriously ill patients may undergo distressing interventions until death. Objectives: To investigate the feasibility of using the Surprise Question, “Would you be surprised if this patient died within the next year?” to identify patients who would benefit from early Serious Illness Conversations and study any changes in the interdisciplinary team’s beliefs, confidence, and engagement as a result of asking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Our study shows that different diagnoses, such as cancer and heart failure, could make it more challenging to identify patients in need of SIC. This was also shown in another study [33], in which they found that by using the surprise question, only six of 23 patients were identified. They also found issues with the feasibility of different prognoses and situations [33].…”
Section: Discussionsupporting
confidence: 61%
“…Our study shows that different diagnoses, such as cancer and heart failure, could make it more challenging to identify patients in need of SIC. This was also shown in another study [33], in which they found that by using the surprise question, only six of 23 patients were identified. They also found issues with the feasibility of different prognoses and situations [33].…”
Section: Discussionsupporting
confidence: 61%
“…Billie and Letizia [ 39 ] wrote that there were ‘several situations in which a case manager evaluated the patient as appropriate for an SI [serious illness] conversation, although he or she did not meet the established SI criteria’ (p. 226). Other studies also indicated ambiguity surrounding eligibility criteria, for example, variation in the interpretation of clinical characteristics [ 34 ] and differences in understanding what constituted a ‘serious illness’ [ 50 ]. Uncertainty surrounding the ideal timing of the conversation, and lack of time to have the conversation, were also stated to be barriers to identification, as recruitment could be limited by patient number or urgency [ 12 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, among larger, sicker patient groups, the SQ could be inadequate or difficult to operationalize [ 12 ]. It was suggested that relying solely on the SQ could overlook some patients who would benefit from a palliative approach [ 25 , 26 , 50 ]; similarly, replying ‘no’ to the SQ was not always thought to require a serious illness conversation [ 50 ]. Triggering criteria for a conversation did not guarantee that a conversation would be held, and without a structured tracking system it could be difficult for clinicians to know who had, or had not, completed serious illness conversations [ 35 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations